2020
DOI: 10.1371/journal.pone.0242182
|View full text |Cite
|
Sign up to set email alerts
|

Electronic health record analysis identifies kidney disease as the leading risk factor for hospitalization in confirmed COVID-19 patients

Abstract: Background Empirical data on conditions that increase risk of coronavirus disease 2019 (COVID-19) progression are needed to identify high risk individuals. We performed a comprehensive quantitative assessment of pre-existing clinical phenotypes associated with COVID-19-related hospitalization. Methods Phenome-wide association study (PheWAS) of SARS-CoV-2-positive patients from an integrated health system (Geisinger) with system-level outpatient/inpatient COVID-19 testing capacity and retrospective electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 20 publications
2
41
0
3
Order By: Relevance
“…Using data from a cohort of tested/diagnosed COVID-19 patients at MM, we performed what we believe is the first PheWAS looking at multiple COVID-19 outcomes stratified by race. A recently published PheWAS by Oetjens et al found 21 phenome-wide significant traits—including six kidney (e.g., end stage renal disease or stage 5 CKD [OR = 11.07, p = 1.96 × 10 −8 ]), six cardiovascular (e.g., congestive heart failure [OR = 3.8, p = 3.24 × 10 −5 ]), five respiratory (e.g., chronic airway obstruction [OR = 2.54, p = 3.71 × 10 −5 ]), and three metabolic (e.g., type 2 diabetes [OR = 1.80, p = 7.51 × 10 −5 ]) phenotypes—associated with COVID-19-related hospitalization, which is consistent with our results [ 14 ]. This technique allowed us to explore and identify potentially associated conditions across the medical phenome that are associated with susceptibility, hospitalization, ICU admission or mortality.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Using data from a cohort of tested/diagnosed COVID-19 patients at MM, we performed what we believe is the first PheWAS looking at multiple COVID-19 outcomes stratified by race. A recently published PheWAS by Oetjens et al found 21 phenome-wide significant traits—including six kidney (e.g., end stage renal disease or stage 5 CKD [OR = 11.07, p = 1.96 × 10 −8 ]), six cardiovascular (e.g., congestive heart failure [OR = 3.8, p = 3.24 × 10 −5 ]), five respiratory (e.g., chronic airway obstruction [OR = 2.54, p = 3.71 × 10 −5 ]), and three metabolic (e.g., type 2 diabetes [OR = 1.80, p = 7.51 × 10 −5 ]) phenotypes—associated with COVID-19-related hospitalization, which is consistent with our results [ 14 ]. This technique allowed us to explore and identify potentially associated conditions across the medical phenome that are associated with susceptibility, hospitalization, ICU admission or mortality.…”
Section: Discussionsupporting
confidence: 90%
“…Only a handful of pre-existing comorbidities are known to be associated with experiencing adverse COVID-19-related outcomes. These pre-existing conditions include liver, kidney, heart, and respiratory disease [ 2 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 patients with hypertension or cardiovascular disease are 3-4 times more likely to develop severe disease compared to those without pre-existing conditions [56, 57•]. Additionally, patients with chronic kidney disease (CKD) have COVID-19 hospitalization and mortality rates 11 and 14 times higher than the general population, respectively [58,59]. Black individuals have the highest prevalence of hypertension and CKD of any racial and ethnic group in the USA, with 57.1% of Black adults reporting hypertension in 2018 [60][61][62].…”
Section: Hypertension Cardiovascular Disease and Chronic Kidney Diseasementioning
confidence: 99%
“…17 Due to its effects on J o u r n a l P r e -p r o o f the immune system, kidney disease also impairs recovery from acute infections as demonstrated by the four-fold increased risk of hospitalization and mortality with COVID-19. [18][19][20] In fact, one of the earliest reported deaths attributed to COVID-19 in the U.S. was a patient receiving hemodialysis. 21 The impact of kidney disease on mortality is also likely underestimated because more than 80% of kidney disease is not recognized, diagnosed, treated, or recorded as a cause of death.…”
Section: Scope Of Problemmentioning
confidence: 99%